Proceedings of the International Conference on Transformations and Innovations in Management 2017
DOI: 10.2991/ictim-17.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Profit Transferring of Multinational Enterprises in the Chinese Industry by Transfer Pricing

Abstract: Decentralized enterprises, such as multinational enterprises (MNEs), adopt transfer prices to coordinate the strategies of the operating functional divisions and marketing divisions in a multinational environment. This paper analyzes the existence of profit transfer though transfer pricing among MNEs in China, and employs quantitative analysis to evaluate the amount of profit that is transferred by this mechanism in the Chinese industry. The contradiction between MNEs' abundant advantages of operating in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Moreover, companies that associate their executives' salaries with corporate profits show significantly higher profits and the higher the percentage of ownership by the Chinese government, the lower the level of declared profitability. Sun, Li, and Zheng (2017) used official statistics to determine whether there is a difference in profitability between multinational companies operating in China and domestic companies. In their analysis, they used corporate profits as a dependent variable and found that multinational corporations operating in China made an estimated profit transfer of 21% of their total profits.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, companies that associate their executives' salaries with corporate profits show significantly higher profits and the higher the percentage of ownership by the Chinese government, the lower the level of declared profitability. Sun, Li, and Zheng (2017) used official statistics to determine whether there is a difference in profitability between multinational companies operating in China and domestic companies. In their analysis, they used corporate profits as a dependent variable and found that multinational corporations operating in China made an estimated profit transfer of 21% of their total profits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the respective tax administrations enact laws and enforce regulations on the documentation of intragroup transactions and the control of the profit transfers, to comply with the "Arm's Length Principle". According to this principle the price of each transaction should be regulated as if the companies involved were in fact independent as opposed to adjusting prices for the benefit of the same corporate structure (Sun, Li, and Zheng, 2017).…”
Section: Introductionmentioning
confidence: 99%